Control of speed during the double poling technique performed by elite cross-country skiers - Lindinger, S. J.; Stöggl, T.; Müller, E.; Holmberg, H. C. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Double poling (DP) as a main technique in cross-country skiing has developed substantially over the last 15 yr. The purpose of the present study was to analyze the question, "How do modern elite skiers control DP speed?"